KARAKTERISTIK SENYAWA ALKANOLAMIDA DARI MINYAK JARAK CASTOR DAN DIETANOLAMINE DENGAN KATALIS KOH - Fatma Sari Lubis (JURNAL KONVERSI, 2018)
Alkanolamide is an amide compound widely used in chemical, cosmetic and automotive industries. This compound has a "detergency" property because it has an amphilic molecule. the raw material that used is methyl esters, but the use of methyl esters needs to be considered because it can cause excessive foam in its use. This study uses castor oil as a raw material for triglycerides. Because of its nature, the alkanolamide can act as a surfactant. Hence, the surfactant of alkanolamide type environmentally-friendly and biodegradable surfactant from renewable sources. This study aims to identify amide compounds from reaction between triglyceride and diethanolamine with KOH catalyst. From the FTIR analysis result, the C=O compound formed has a wavelength 1618,88 cm-1, the best result of GC-MS is the compound diethanolamide oleat with 38% similarity.